2014
DOI: 10.1002/nme.4787
|View full text |Cite
|
Sign up to set email alerts
|

Interface problems with quadratic X-FEM: design of a stable multiplier space and error analysis

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 47 publications
0
21
0
Order By: Relevance
“…The case of linear F (x) is slightly different, due to its link with the geometrical approximation of the level sets and more particularly of the interface established at the end of "Enrichment functions for weak discontinuities" section. Ferté et al [45,46] showed for strong discontinuities that the approximation of the level set impacts the expected theoretical convergence rates, in the case of quadratic elements: 2 is expected if a quadratic approximation of the level set is used (equivalently quadratic F (x)), while 1.5 is expected if a linear representation of the level set is used (equivalently linear F (x)). To illustrate this behavior, we also considered two models based on the enrichment designed for strong discontinuities, using Lagrange multipliers to enforce the continuity of the displacement through the interface: one with quadratic shape functions and a linear approximation of the level set and one with quadratic shape functions and a quadratic approximation of the level set.…”
Section: Circular Inclusion With Imposed Displacementmentioning
confidence: 99%
“…The case of linear F (x) is slightly different, due to its link with the geometrical approximation of the level sets and more particularly of the interface established at the end of "Enrichment functions for weak discontinuities" section. Ferté et al [45,46] showed for strong discontinuities that the approximation of the level set impacts the expected theoretical convergence rates, in the case of quadratic elements: 2 is expected if a quadratic approximation of the level set is used (equivalently quadratic F (x)), while 1.5 is expected if a linear representation of the level set is used (equivalently linear F (x)). To illustrate this behavior, we also considered two models based on the enrichment designed for strong discontinuities, using Lagrange multipliers to enforce the continuity of the displacement through the interface: one with quadratic shape functions and a linear approximation of the level set and one with quadratic shape functions and a quadratic approximation of the level set.…”
Section: Circular Inclusion With Imposed Displacementmentioning
confidence: 99%
“…The choice of the V h and M h has to satisfy a uniform inf-sup condition [4] with respect to suitable norms. In the present study, as in [3,8], the following mesh-dependent L 2 norms are considered:…”
Section: Discretizationmentioning
confidence: 99%
“…As in [8,10], the Lagrangian multiplier components are defined on the parent nodes belonging to K h . They are based on the same linear shape functions N i .x/ that are used for the displacement field.…”
Section: Discretization Of the Lagrangian Multipliersmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, new models such as TLS (Thick Level Set) approach, developed by [17], permit the description of initiation and propagation of defects in a unified framework [18]. However, the introduction of partial inter-facial cracks is not fully established yet, even if there is many promising works on this subject [19][20]. In addition, all these models and approaches to solve the problem may be too heavy to be contained in practical software.…”
Section: Introductionmentioning
confidence: 99%